The Role of Task-Based Language Teaching in Improving Speaking Skills of Uzbek EFL Learners (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Task-Based Language Teaching (TBLT) has emerged as an influential approach within TESOL, emphasizing real-life communication and learner-centered instruction. This study explores the role of TBLT in enhancing speaking skills among Uzbek learners of English as a Foreign Language (EFL). Traditional teaching methods in Uzbekistan often focus on grammar and translation, which limit opportunities for authentic communication. By contrast, TBLT encourages learners to use English through interactive tasks such as role-plays, problem-solving activities, and collaborative projects. Data from classroom observations and learner feedback reveal that students engaged in TBLT demonstrate improved fluency, greater confidence, and higher levels of participation. Moreover, TBLT reduces speaking anxiety by shifting the focus from accuracy to meaningful communication, allowing learners to express themselves more freely. The findings suggest that incorporating TBLT into EFL classrooms in Uzbekistan can bridge the gap between theoretical knowledge and practical language use. This study concludes that TBLT not only fosters communicative competence but also aligns with global TESOL standards, thereby contributing to the overall improvement of English language education in Uzbekistan.